Referências profissionais para psicólogos atuarem na política pública de saúde - Carvalho, Talita Fabiano de (2023)
Working in the health area, especially in the public sector, requires an intense understanding of the phenomena that permeate the relationship between the subjects' physical and/or mental illness processes and their preparations. In addition, it requires in-depth knowledge of the guidelines of this public health policy and its legal, citizen and constitutional provisions. The performance of psychologists in the area of Health requires beyond the aforementioned technical-scientific and ethical knowledge. Thinking about the skills and competences necessary for this action is not only necessary, but essential, based on the ethics and social commitment of Psychology, on a deep self-knowledge and community involvement working in the uncompromising defense of human rights. The aim of this project was to identify and analyze the skills and abilities of the psychologist's role in the context of public health policy in the State of São Paulo. The project has two stages, the first being the construction of an instrument to identify skills and competences and the second being applied to Psychology professionals working in the SUS and analysis of the results. This was a descriptive, exploratory and cross-sectional study. Meaning analysis of the interviews was performed in addition to descriptive statistics to characterize the results. Based on these parameters and the temporal context, which runs through the history of Psychology and psychologist training, the interfaces between Psychology and Health from the perspective of the SUS, the expressions between Hospital Psychology and Health Psychology, and ethics in the exercise professional recognizing and listening to the other. The universe surveyed was quite small, given the dimension of Psychology professionals who operate in the Health area, which is around 19% of the professionals working in Brazil, which currently have more than 416 thousand subscribers, however as the study dealt with professional practice, it allowed us discoveries that we believe are relevant and useful to qualify the profession's performance.